(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2025)
Abstract - The coal handling system functions to handle work starting from unloading coal from ships/barges (unloading area) which is moved to conveyors, stockpiling/storage in stock areas, or filling into bunkers used for combustion in boilers. During the dismantling process, blockages / plugging should not occur, especially in the chute conveyor, therefore a protection sensor is needed to prevent this. The old sensor used was a Tilt Switch type which during use was ineffective due to many problems so maintenance was carried out, as a result it was replaced using an MBD (Microwave Beam Detector) type sensor. From the analysis after replacement using the MBD sensor, the problem of chute blockage is reduced, as can be seen from the reduced maintenance frequency.